Delivery LL37 by chitosan nanoparticles for enhanced antibacterial and antibiofilm efficacy. (1st September 2022) - Rashki, Somaye; Safardoust-Hojaghan, Hossein; Mirzaei, Hamed; Abdulsahib, Waleed K.; Mahdi, Makarim A.; Salavati-Niasari, Masoud; Khaledi, Azad; Khorshidi, Ahmad; Mousavi, Seyyed Gholam Abbas
Abstract: In this study, the fabrication of LL37-loaded chitosan nanoparticles (CS/LL37-NPs) was based on an ionotropic gelation method between sodium tripolyphosphate (TPP) and chitosan. Synthesized chitosan nanoparticles (CS-NPs) were approved by Fourier Transform Infrared (FTIR), UV–vis spectroscopy, Dynamic Light Scattering (DLS), Scanning Electron Microscope (SEM), and Transmission Electron Microscopy (TEM). The encapsulation efficiency of LL37 in this delivery system (CS/LL37-NPs) was 86.9%. According to in vitro release profile, the release of LL37 from CS/LL37-NPs was almost complete after 5 days. Additionally, CS/LL37-NPs can cause an increase in the half-life and prolonged LL37 antibacterial activity against Methicillin-resistant Staphylococcus aureus (MRSA). This delivery system demonstrated 68% biofilm formation inhibition compared to the LL37 alone. Also, icaA gene expression in the face of CS/LL37-NPs was significantly decreased. This study showed the important role of delivery systems in enhancing LL37 antibacterial and antibiofilm activity which can be suggested as a promising agent in the inhibition of bacterial growth and the prevention of biofilm formation. Highlights: Fabrication of encapsulation of LL37 into chitosan nanoparticles Characterization of product by FTIR, SEM and TEM techniques The excellent antibacterial and antibiofilm activity of encapsulation of LL37 into chitosan nanoparticles LL37 loaded chitosan nanoparticles demonstrated good in-vitro release profiles. Increased half-life and prolonged LL37 biological activity